Construction of a Vibrio alginolyticus hopPmaJ (hop) mutant and evaluation of its potential as a live attenuated vaccine in orange-spotted grouper (Epinephelus coioides). Issue 76 (May 2018) - Pang, Huanying; Qiu, Mingsheng; Zhao, Jingmin; Hoare, Rowena; Monaghan, Sean J.; Song, Dawei; Chang, Yunsheng; Jian, Jichang
Abstract: Vibrio alginolyticus, a bacterial pathogen in fish and humans, expresses a type III secretion system (T3SS) that is critical for pathogen virulence and disease development. However, little is known about the associated effectors (T3SEs) and their physiological role. In this study, the T3SE gene hopPmaJ ( hop ) was cloned from V. alginolyticus wild-type strain HY9901 and the mutant strain HY9901Δ hop was constructed by the in-frame deletion method. The results showed that the deduced amino acid sequence of V . alginolyticus HopPmaJ shared 78–98% homology with other Vibrio spp. In addition, the HY9901Δ hop mutant showed an attenuated swarming phenotype and a 2600-fold decrease in the virulence to grouper. However, the HY9901Δ hop mutant showed no difference in morphology, growth, biofilm formation and ECPase activity. Finally, grouper vaccinated via intraperitoneal (IP) injection with HY9901Δ hop induced a high antibody titer with a relative percent survival (RPS) value of 84% after challenging with the wild-type HY9901. Real-time PCR assays showed that vaccination with HY9901Δ hop enhanced the expression of immune-related genes, including MHC-Iα, MHC-IIα, IgM, and IL-1 β after vaccination, indicating that it is able to induce humoral and cell-mediated immune response in grouper. These results demonstrate that the HY9901Δ hop mutant could be used as an effective live vaccine to combat V. alginolyticus in grouper. Highlights: The biological functions of HopPmaJ in alginolyticus were investigated. HY9901Δ hop suppressed swarming motility, adhesion and virulence. The RPS of grouper vaccinated with HY9901Δhop was 84%. HY9901Δ hop could stimulate innate and acquired immune responses in E. coioides.